PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN AGAMA KRISTEN MELALUI METODE BELAJAR KELOMPOK DAN TANYA JAWAB KELAS VI SDN 164522 KOTA TEBING TINGGI - Tiur Butar-Butar (Universitas Negeri Medan, 2015)
The purpose of this research is to improve learning motivation of Christian education by the use of group learning and discussioon in the learning process of VI grade SDN 164522 Tebing Tinggi in academic. This research use two cycles. The subject of this research were all student of VI grade SDN 164522 Tebing Tinggi which amounted 10 students of 4 male students and 6 female students. The method used is group discussion method question and answer method and lecture method .The result of the research showed that learning motivation to christian education of VI grade can improve. This is demonstrated by the increase in the average of score motivation at first cycle (70 %) to 100 % in second cycle. Key word : group learning, discussion, lecture